Readmission in children's emergency care: an analysis of hospital episode statistics. Issue 5 (21st September 2009) - Callery, Peter; Kyle, Richard G; Campbell, Malcolm; Banks, Michele; Kirk, Susan; Powell, Peter
Abstract : Aim: To compare rates of emergency readmission following discharge for common paediatric conditions from a range of hospital services. Design: Retrospective analysis of hospital episode statistics (HES) and telephone survey of service provision. Setting: Twelve hospitals serving a metropolitan area in the North West of England. Outcome measures: Emergency admissions to hospital within 7 days of discharge for breathing difficulty, feverish illness and/or diarrhoea. Results: HES were obtained for all children under 15 years of age discharged following emergency admission for breathing difficulty, feverish illness and/or diarrhoea during 2005/2006 (n=20 354) or 2006/2007 (n=23 018). The readmission rate for all hospitals in 2006/2007 was 5.5%. The percentage of same day discharges was associated with readmission (Kendall's taub correlation=0.61, p=0.007). Readmissions were also associated with the proportion of same day discharges for breathing difficulty (Kendall's taub =0.83, p<0.001) and feverish illness (Kendall's taub =0.50, p=0.023) but not significantly so with diarrhoea (Kendall's taub =0.37, p=0.098). The total number of admissions at a hospital in the year was associated with its readmission rate (Kendall's taub =0.71, p=0.002). Most of the sample lived in the 40% most deprived areas in England, but there was no significant association between readmission and living in the 10% most deprived areas. Conclusions: Readmission rates are associated with higher numbers of annual admissions and higher proportions of children discharged on the day of admission. Variations between hospitals suggest that other factors can also affect readmission rates. Readmission rates calculated from HES can contribute to assessments of the outcome of emergency services.